2018
DOI: 10.1590/1516-3180.2017.0233011017
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 genetic diversity and resistance to antiretroviral drugs among pregnant women in Ribeirão Preto (SP), Brazil. Cross-sectional study

Abstract: The results showed that subtype B predominated, while there was low prevalence of sequences with transmitted drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In contrast to this finding, low levels of PDR among pregnant women [ 19 ] and ART-naive adult individuals [ 23 ] were reported previously from the same study area. Similarly, a study done in Brazil among ART-naive pregnant women indicated a lower PDR detection rate [ 24 ]. In addition to the above previously published data from Ethiopia, this finding is in agreement with studies done in India [ 25 ], Brazil [ 26 28 ], China [ 29 ], and Iran [ 30 ], which reported a moderate magnitude of PDR among HIV-1 antiretroviral adults.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this finding, low levels of PDR among pregnant women [ 19 ] and ART-naive adult individuals [ 23 ] were reported previously from the same study area. Similarly, a study done in Brazil among ART-naive pregnant women indicated a lower PDR detection rate [ 24 ]. In addition to the above previously published data from Ethiopia, this finding is in agreement with studies done in India [ 25 ], Brazil [ 26 28 ], China [ 29 ], and Iran [ 30 ], which reported a moderate magnitude of PDR among HIV-1 antiretroviral adults.…”
Section: Discussionmentioning
confidence: 99%